Philippine Social Constructs Found in Bob Ong’s Stories - Josephine May Grace Aclan Famoso (Ahmad Dahlan Journal of English Studies, 2021)
Literary texts are products of an ideology. Consequently, some Filipinos write about social constructs to uncover and question the existence of a particular social norm. Bob Ong, a Filipino writer, makes readers experience factual events. His novels Macarthur and Kapitan Sino uphold the cultural, economic, and political constructs which made these works vulnerable to be examined from a socio-political perspective. This study used the qualitative-descriptive methodology to show different social classes, conflicts, and resolutions found in the novels. This study also features the ills of society as a reflection of the Philippine society. The following conclusions are drawn: First, that the Philippine social construct can be interpreted based on the Class Conflict theory from the ideology of Karl Marx. Thus, social classes are classified as bourgeoise and proletariat. Second, conflicts are societal in nature and are challenging to resolve. Indeed, the novels reveal concerns that reflect the contemporary Philippine circumstance.